Are individuals with entrepreneurial characteristics more likely to engage in destruction? An experimental investigation among potential 21st century entrepreneurs in Tunisia. (11th June 2019) - El Harbi, Sana; Grolleau, Gilles; Sutan, Angela; Ben Ticha, Zeyneb
Abstract: We test experimentally whether individuals high in some entrepreneurial characteristics are more likely to engage in destructive behavior than other individuals. In the joy‐of‐destruction game, participants can either preserve or costly burn the endowment of each other. In some treatments they can hide from other participants whether they are responsible for destruction. We found that participants high in some entrepreneurial characteristics are significantly more likely to adopt destructive behaviours.